Radiation dose variability in critical thoracic organs during CT imaging: A multi-centre phantom dosimetry study - Kesmezacar, Fahrettin Fatih; Gunay, Osman; Kayaokay, Duygu Tuncman; Yeyin, Nami; Demirci, Ali; Karacam, Songul Cavdar; Oksuz, Didem Colpan; Demir, Mustafa; Almisned, Ghada; Karadag, Teoman; Alkarrani, Hessa; Issa, Bashar; et al. (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
This multicenter phantom-based study quantified organ-specific radiation doses delivered during routine thoracic CT using five clinical systems from four major manufacturers. A total of 70 TLD-100 dosimeters were calibrated and strategically positioned in an Alderson Rando (R) phantom to measure absorbed doses in the lungs, heart apex, atrium, and bilateral breasts. Marked dose variability was observed across scanners, driven by differences in tube current, CTDIvol, pitch, and the implementation of dose modulation strategies. Lung doses ranged from 4.60 to 22.51 mGy, heart apex doses from 4.15 to 23.15 mGy, atrial doses from 4.73 to 20.77 mGy, and breast doses from 3.17 to 22.01 mGy. The CT-2 system consistently yielded the highest organ doses, while the CT-1 demonstrated the most effective dose reduction. Comparative assessment with literature confirmed strong alignment of our measured values with published experimental and Monte Carlo-based studies. It can be concluded that significant dose reductions to radiosensitive thoracic organs are achievable through advanced modulation technologies and tailored protocol adjustments.
Keywords: Thorax CT; Organ dose assessment; Phantom study; Multicenter dose variability; Radiation dose optimization; CHEST CT; COMPUTED-TOMOGRAPHY; OPTIMIZATION; STRATEGIES; PATIENT; RISK; Chemistry; Nuclear Science & Technology; Physics